Oxidative enzymes from newly local strain Aspergillus iizukae EAN605 using pumpkin peels as a production substrate: optimized production, characterization, application and techno-economic analysis - Noman, Efaq; Al-Gheethi, A. A.; A. Talip, Balkis; Mohamed, Radin; Kassim, Amir Hashim (Elsevier, 2020)
The present study deals with optimizing, producing, characterizing, application and techno- economic analysis of oxidative enzymes [Laccase (Lac), manganese peroxidase (MnP), and lignin peroxidase (LiP)] from Aspergillus iizukae EAN605 in submerged fermentation process using pumpkin peels as a production substrate. The best operating parameters for producing Lac, MnP and LiP (6.15, 2.58 and 127.99 U mg−1 respectively) were recorded with 20 g 100 mL−1 of substrate, 4.6 mL 100 mL−1 of inoculum size at pH 5.5 after 10 days. The crude enzyme exhibited high stability at pH (3–9) and temperatures (20−60 °C). Km (Michaelis–Menten) of Lac, MnP and LiP crude enzyme was 2.25, 1.79 and 0.72mM respectively. The decolourization of Remazol Brilliant Blue R by the crude enzyme was 84.84 %. The techno-economic analysis was assessed for a production unit with an annual operating time for enzymatic production and application is 7920 h/year and 100 m3 of the capacity. The process would produce 27,000 cm3 of crude enzyme with a price of USD 0.107 per cm3 compared to USD 1 per cm3 of the current commercial enzyme. The findings indicated that pumpkin peels have potential as a production substrate for oxidative enzymes from A. iizukae EAN605 and is economically feasible.